2021
DOI: 10.18632/aging.203250
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of an immune-related ceRNA network in identifying a novel lncRNA signature as a prognostic biomarker for hepatocellular carcinoma

Abstract: The function of competitive endogenous RNA (ceRNA) network in the immune regulation of hepatocellular carcinoma (HCC) is unclear. Our study aimed to construct an immune-related ceRNA network and develop an immune-related long noncoding RNA (lncRNA) signature to assess the prognosis of HCC patients and to optimize the treatment methods. We firstly constructed a ceRNA regulatory network for HCC using differentially expressed lncRNAs, mRNAs and microRNAs (miRNAs) from the Cancer Genome Atlas. A signature was cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The expression level of ICB-related genes was closely involved with the outcome of immunotherapy. Therefore, the Spearman correlation between the 11 ICB-related genes and risk score was analyzed [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The expression level of ICB-related genes was closely involved with the outcome of immunotherapy. Therefore, the Spearman correlation between the 11 ICB-related genes and risk score was analyzed [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among them, lncRNA was the most reported type, so the present study takes it as an example to introduce signature construction and verification methods. First, the prognostic value of lncRNAs involved in the cancer-specific ceRNA network can be evaluated by univariate Cox regression analysis of the association between lncRNA expression level and patient survival time ( 69 ). Then, lncRNA-related prognostic signature was commonly established by performing LASSO Cox regression analysis or multivariate Cox regression analysis ( 70 ).…”
Section: Computational Establishment Of Cerna Network-based Prognosti...mentioning
confidence: 99%
“…Based on GSEA results, Chen et al. ( 69 ) found that the constructed eleven-lncRNA prognostic signature was involved in immune-related processes of hepatocellular carcinoma.…”
Section: Computational Establishment Of Cerna Network-based Prognosti...mentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence have shown that the ceRNA crosstalk participates in indispensable regulatory processes and its perturbation will scramble the balance of cell regulatory system, resulting in disease initiation and tumor occurrence. In HCC, ceRNA networks aided the prioritization of RNA biomarkers including miRNA 12 and lncRNA 13 by comparing normal controls with tumor patients. As previously mentioned, the regulatory peculiarity of TP53 granted its capability in orchestrating complicated biological processes.…”
Section: Introductionmentioning
confidence: 99%